QUALITY ANALYSIS OF SUPPORT MARKETING AND QUALITY OF SALES TRAINING ON SALES PERFORMANCE CAPABILITY ON PERFORMANCE SALES PERFORMANCE - Hapsari, Ria Mawar; Indriani, Farida; Sutopo, Sutopo (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2017)
This study aims to analyze and examine the effect of quality marketing support, sales quality, sales force capability to salespeople performance, with the formulation of the problem of "how to improve sales force performance" on channel Direct Sales Credit Card at BNI Semarang and Yogyakarta Regional Office. Populations and samples selected in the study were credit card sales BNI channel Direct Sales Semarang and Yogyakarta, which amounted to 110 respondents, with the census method. Data collection using questionnaire with answer value 1 (very strongly disagree) up to 10 (very strongly agree). Data analysis using Structural Equation Modeling (SEM) through AMOS program, with result indicate that research model acceptable, goodness of fit index as follows: Chi Square = 126,774; Probability = 0.177; RMSEA = 0.033; GFI = 0.885; AGFI = 0.845; TLI = 0.984; and CFI = 0.987. The conclusions of this study indicate that sales force capability can affect salesperson performance by looking at the quality of marketing support. This study also shows that sales force capability can affect salesperson performance by looking at the quality of sales training.